Contribution Isolation of LUCC Impact on Regional PM2.5 Air Pollution: Implications for Sustainable Land and Environment Management - Ding, Ying; Feng, Huihui; Zou, Bin; Ye, Shuchao (Frontiers in Environmental Science, 2022)
Understanding of the contribution of LUCC to air pollution is the basis for land management and air pollution control. This study aimed to estimate the contribution of LUCC to PM2.5 pollution levels in the Changsha-Zhuzhou-Xiangtan (CZT) urban agglomeration in the central south China. Methodologically, residual analysis was adopted to isolate the LUCC contribution with the aid of multiple datasets from satellite observations and reanalysis products. The results revealed that the PM2.5 concentration increased significantly from 2001 to 2008 and then decreased. LUCC tended to enhance both the increasing and decreasing trends, while the magnitudes varied under different climate conditions. During 2001–2008, LUCC exerted more important influence on the air pollution, which contributed 40.59% of the total increase. During 2008–2014, the changing climate enhanced air pollution removal. During this time, the government of the CZT proposed the “Two Oriented Society” policy for sustainable urban development. Under this condition, the LUCC accounted for only 25.66% of the total PM2.5 decrease. This result suggested that it is necessary to further strengthen the goal of sustainable development rather than following the traditional way of “governance after development”.